LAYANAN PENDIDIKAN AGAMA SESUAI AGAMA SISWA DI SEKOLAH - Hayadin Ode Hayadin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
This research aimed to describe the best practice of religious education at schools. As many cases has been blown up by the medias, that religious education at schools took place discriminately where the minority religiously student haven’t ever got service according to theirs and by the same religious teacher. This research found that there were any best practiced at schools that serve religious education according to student’s religious and by the same teacher. These cases were founded at: SMA Labschool Jakarta, SMA Katholik Santo Joseph Denpasar, SMA Ananda Bekasi, SMA SLUA Denpasar, SMK Gloria Manado, SMPN 2 Ende Flores, SMPN 1 Ambon, SMAN 1 Denpasar, SMAN 1 Bogor, SMAN 1 Manado, SMK Singkawang, and SMK Bangkabelitung. Data collected through qualitative approach using interview, observation, and relevant document study, and listed questions as well. The research conducted at 2015 at such location mentioned. Any persons and figures that the data and information derived from were head schools, religious teachers, school staffs, school committees, and students as well. The research concluded that religious education at such schools has been served according to student’s religion, and by the same religious teachers. Religious teachers recruited either by government, local government, head schools with agreement of school committee or by foundation that lead the schools.